THỬ NGHIỆM KHẢ NĂNG ỨC CHẾ NẤM SỢI TRÊN KÍNH QUANG HỌC CỦA BIOXIT AIT - Nguyễn, Thu Hoài; Ngô, Cao Cường; Chu, Thanh Bình; Iu.L., Kovaltruc (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EXAMINATION OF CAPABILITY AGAINST MOLDS ON OPTICAL EQUIPMENTS BY BIOXIT AITTropical climates is suitable for growing molds. Optical equipments can be damaged by molds in the storage or use condition. 18 strains fungi belong to 14 different genera in optical instrument of factory 23/Z199 we are isolated. In the development, pH of culture was changed by these strains from neutral to acid, in that there are 4 genera Aspergillus niger QH2306 - pH 2,56; Aspergillus oryzae QH2302-pH 4,95; Penicillium lanoso QH2308 pH 4,85 and Chaetomium globosum QH2316 - pH 4,19. Prevented molds from growing in optical equipments we tested volatile inhibitor Allyl isothiocyanate (AIT) and applied this biocide AIT for protection optical equipments at humic 97%, temperature 28 ± 2oC, Minimum Inhibitory Concentration (MIC) is 0,001mg/m3. After 28 days tested, molds could not growed in optical instrument and the technical parameter of optical instrument was changed by molds.